Holger Pedersen. Road-map to the Indian´s Treasure. -On the Chilean meteorite Vaca Muerta and its early mistake for silver Norderstedt: Book on Demand, 2012. 300 pp. - Soto Villaflor, Raúl (Revista de Geografía Norte Grande, 2021)
NO RESENTA RESUMEN